Ms Davis : a graphic biography - Titeux de la Croix, Sybille (Fantagraphics Books, Inc., 2023)
"In 1971, the FBI put Angela Davis on their 10 Most Wanted List because they alleged that she orchestrated a politically motivated Marin County courtroom gunfight. She went to prison despite her protestations of innocence. Soon the entire world would know her story and demand her freedom. In 1972, she was found not guilty by an all-white jury. Ms Davis is the story of her dedication to the fight for justice"--